Developing Islamic Board Games Based on Local Wisdom to Teach Daily Manners in Early Childhood - Irmawati Irmawati; Siti Ratnawati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Early childhood education plays a vital role in character development, particularly in instilling moral and Islamic values such as daily manners. However, current teaching methods often rely on verbal instruction, which lacks engagement and contextual relevance. This study addresses the need for innovative, culturally grounded, and enjoyable learning media. This research employed a Research and Development (RD) approach based on a modified Borg Gall model. The study involved 30 Group B children from Ihsaniah Bangun Galih Kindergarten in Central Java, Indonesia. The development process included six stages: identifying needs, data collection, product design, expert validation, limited trials, and product revision. Data were collected through observation, interviews, and expert validation questionnaires, and analyzed using both quantitative and qualitative methods. The resulting product was an Islamic board game that integrated daily manners content with local wisdom. Expert validation yielded a high feasibility score (88.8%), and limited trials showed positive outcomes: 80% of children could recall relevant prayers, and 73% demonstrated improved manners. Teachers noted increased student engagement and ease of integration into thematic lessons. The findings suggest that Islamic board games based on local culture are effective tools for teaching manners in early childhood. The combination of play-based learning and cultural relevance enhances children's moral development and engagement.